PERAN ORANG TUA DALAM MENINGKATKAN MOTIVASI BELAJAR PENDIDIKAN AGAMA PADA ANAK - Syarifah Rahmi (AZKIA : Jurnal Aktualisasi Pendidikan Islam, 2022)
This thesis is entitled The Role of Parents in Increasing Religious Education Learning Motivation in Children in Bangkeh Village, Geumpang District. The purpose of this study was to determine the role of parents in motivating children to learn religious education, to find out the obstacles faced by parents in motivating their children, and to determine the effect of parental care on increasing motivation to learn religion in children in Bangkeh village, Geumpang sub-district. . This research was conducted in Bangkeh village, using library research and field research using documentation, observation, interviews and distributing questionnaires to parents. The results showed that in motivating children to study religion, parents in Bangkeh village, Geumpang sub-district, entrust their children to pesantren to learn the Koran, buy books to be a source of reading in studying at school and provide punishment for children who are sometimes a little lazy in studying at home. While the obstacles for parents in educating and motivating are the lack of interest in the children themselves in learning religion and in children who are sometimes a little naughty and do not obey their parents. The influence of parental guidance has a great influence where children become enthusiastic and more active in learning religious education so that the values ​​and understanding obtained by children in learning are very satisfying and also the behavior of children in the family is getting better.